Pengaruh Berbagai Media Tanam Terhadap Pertumbuhan Bibit Bulbil Tanaman Porang (Amorphophallus oncophyllus P.) - Yulianti, Misa; Syamsuwirman; Badal, Bustari (Fakultas Pertanian, Universitas Ekasakti, 2025)
Research on the effect of various planting media on the growth of porang bulbil seedlings has been carried out in Korong Gadang Village, Kuranji, Padang, December 2021-March 2022. The study used RAL with 6 treatments and 5 replications, so 30 experimental units, each experimental unit 5 plants. Observation data were analyzed statistically by means of variance (F test). If F count > F table, continue using DNMRT. The purpose of this study was to obtain the best growing media for the growth of porang bulbil seedlings. As the treatment of various planting media, namely: Treatment A = 100% Soil; B = Soil: Rice Husk: Compost (1:1:1); C = Soil : Rice Husk : Bokashi Straw (1:1:1); D = Soil : Rice Husk : Bokashi Chicken Manure (1:1:1); E = Soil : Rice Husk : Bokashi Goat Manure (1:1:1); F = Soil : Rice Husk : Bokashi Manure (1:1:1). The results showed that various planting media on porang had significantly different effects on plant height, stem diameter, top wet weight, bottom wet weight, and bottom dry weight, giving significantly different effects on top dry weight, but not significantly different in amount. flyer. Treatment D (soil: rice husk: bokashi chicken manure (1:1:1)) was the best growing medium for bulbil porang breeding. Based on the results of the study, it is recommended to use a planting medium consisting of soil: rice husk: bokashi chicken manure (1:1:1) for porang bulbil breeding.